Pengaruh audit internal dan efektifitas pengendalian internal terhadap deteksi fraud pada perumda air minum wair pu’an Kabupaten Sikka - Aurelia, Pipiet Niken; Dilliana, Siktania Maria; Lamawitak, Paulus Libu; Sanga, Konstantinus Pati (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2022)
This study aims to determine the effect of internal audit and the effectiveness of internal control on fraud detection at PERUMDA Air Minum Wair Pu'an, Sikka Regency. The data collection technique in this study used a questionnaire survey distributed to 33 employees which were then processed using the SPSS program. The analysis method used to test the hypothesis is multiple linear regression analysis. The results of the t statistical test (partial) show that internal audit (X1) has no significant effect on fraud detection (Y) and the effectiveness of internal control (X2) has a significant effect on fraud detection (Y). And based on the F statistical test (simultaneous) shows that internal audit (XI) and Internal Control Effectiveness (X2) together have a significant effect on fraud detection (Y). It can be concluded that internal control in PERUMDA Air Minum Wair Pu'an, Sikka Regency greatly affects the level of fraud in the company, the more effective the internal control system implemented in an entity, the lower the tendency of fraud that may occur.